2019
DOI: 10.5414/cp203382
|View full text |Cite
|
Sign up to set email alerts
|

Effect of triple therapy in patients with asthma-COPD overlap

Abstract: Objective: Asthma-chronic obstructive pulmonary disease (COPD) overlap (ACO) is of increasing interest because ACO patients have significantly worse outcomes, leading to greater social and economic burdens compared with asthma or COPD alone. Some guidelines for ACO recommend triple therapy with inhaled corticosteroids, long-acting β2 agonists, and long-acting muscarinic antagonists. However, this approach is based on extrapolating data from patients with asthma or COPD alone. Therapeutic studies for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 37 publications
0
22
0
1
Order By: Relevance
“…7 We conducted the present study based on physiological lung function criteria described in previous studies. 6,7,10,15,19,33 In contrast, concordance with the proportion of ACO patients in several different studies indicates the validity of the physiological lung function criteria. 5,7,14,19 Further studies are required to establish better diagnostic criteria for ACO.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…7 We conducted the present study based on physiological lung function criteria described in previous studies. 6,7,10,15,19,33 In contrast, concordance with the proportion of ACO patients in several different studies indicates the validity of the physiological lung function criteria. 5,7,14,19 Further studies are required to establish better diagnostic criteria for ACO.…”
Section: Discussionmentioning
confidence: 93%
“…We previously reported the usefulness of dual therapy with ICS/LABA as a maintenance therapy for ACO, 9 and subsequently conducted a study to investigate the effect of triple therapy with ICS/LAMA/LABA. 10 We have also demonstrated the advantage of triple therapy in patients with ACO but did not focus on the IC, an index of inspiratory restraint resulting from hyperinflation of the lung. 28,29 Hyperinflation of the lung is an important finding that causes exertional dyspnea and reduced exercise in patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, it seems fair to point out that, although we believe that the term asthma-COPD overlap (ACO) should be abandoned because it does not identify a clearly independent disease entity and rather indicates asthmatic patients who have smoked or still smoke [39], the view of many specialists is that it is correct to treat patients with ACO who remain symptomatic or suffer from frequent exacerbations with triple therapy despite initial inhaler therapy [40]. A recent pilot study, which compared the efficacy of LAMA/ICS/LABA triple therapy with ICS/LABA dual therapy, showed that 4-week once-daily treatment of ACO patients with umeclidinium 62.5 lg added to fluticasone furoate/vilanterol 200/25 lg produced significant improvements from baseline in lung function compared with once-daily treatment with fluticasone furoate/vilanterol lg alone [41]. It is obvious that more and larger studies are needed to validate such an approach, also possibly using a meta-analytical approach.…”
Section: What Do These Meta-analyses Suggest?mentioning
confidence: 99%